Estrutura da produção editorial de periódicos biomédicos brasileiros - Costa, Antônio Felipe Corrêa da (1988)
The objectives of this study were 1) to know the structure of the editorial production of Brazilian biomedical periodicals from 1827 till 1978, by the analysis of some product characteristics; 2) to develop a new method of studying the production of scienyific periodicals and to evaluate Brazilian production of periodicals that carry one of the editorial area characteristics, the frequent changing of titles without significant changing in the contents. It as made use of a reference book on periodicals as a source of data collecting since it was the most practicable way to know some aspects of the publishing structure of the Biomedical area. A thousand, four hundred and forty ope titles were analysed and a specific handling was given to the subject with inferable statistical data of the analysed source. Periodicals were current, enclosed, interrupted and with unknown publishing aspect. Eight editors were identified: hospital study centers, academic institutions, private research institutes, government offices, learned societies, medical associations, pharmaceutical laboratories, commercial editors and also carne out a large number of titles without information about editors. The production of scientific periodicals in Brazil showed an amateurish and improvised characteristics without the fulfilment of a mínima criteria of stan dardization, which concurs to arise many kinds of problems such as a lack of economic practicability, production quality and the appropriate distribution of titles.